Analisis Pendapatan Pedagang Sayur Keliling dan Pedagang Sayur Menetap di Pasar Tradisional Batu Merah - Tehubijuluw, Valda; Thenu, Stephen F W; Kaplale, Raihana (Universitas Pattimura, 2025)
This research aims to analyze the income of mobile vegetable vendors and stationary vegetable vendors at the Batu Merah Traditional Market.The sample was taken using simple random sampling and purposive sampling, with 13 mobile traders and 17 stationary traders being selected. Using the quantitative analysis method. The research results show that the mobile vegetable vendors earn an income of Rp. 14,720,187 per month, while the stationary vegetable vendors at the Batu Merah Traditional Market earn an income of Rp. 18,768,921 per month.